2000
DOI: 10.1038/sj.onc.1203446
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Myc-dependent apoptosis by eukaryotic translation initiation factor 4E requires cyclin D1

Abstract: Ectopically expressed eukaryotic translation initiation factor 4E (eIF4E) stimulates cell proliferation, suppresses apoptosis in growth factor restricted cells, and induces malignant transformation in primary rodent ®broblasts when coexpressed with protooncogene myc. We report here that eIF4E rescued rat embryo ®broblasts ectopically expressing c-Myc ( signi®cantly increased chemosensitivity; either soluble antisense cyclin D1 oligomers or transfection with a dominant negative cyclin D1 mutant that prevents tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 73 publications
6
81
0
Order By: Relevance
“…As might be expected, eIF4E rescue appears to be pleotropic; mediated by increasing the nuclear-cytoplasmic transport and ribosomal recruitment of numerous transcripts. For example, cells are rescued from oncogene-dependent apoptosis by interdiction of the apoptotic program at the mitochondrial checkpoint by cyclin D1 64 and Bcl-X L . 65 The relative importance of each transcript or repertoire of transcripts encoding candidate downstream effectors and the rules describing their integration into a biological response remains an active area of investigation.…”
Section: Translational Control Of Malignant Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, eIF4E rescue appears to be pleotropic; mediated by increasing the nuclear-cytoplasmic transport and ribosomal recruitment of numerous transcripts. For example, cells are rescued from oncogene-dependent apoptosis by interdiction of the apoptotic program at the mitochondrial checkpoint by cyclin D1 64 and Bcl-X L . 65 The relative importance of each transcript or repertoire of transcripts encoding candidate downstream effectors and the rules describing their integration into a biological response remains an active area of investigation.…”
Section: Translational Control Of Malignant Conversionmentioning
confidence: 99%
“…However, disrupting mTOR-mediated signaling with rapamycin does not restore apoptosis sensitivity to cancer cells harboring aberrantly activated eIF4F or suppress their tumorigenesis. 57,62,64 Direct approaches. Normalizing eIF4F function might be accomplished by disrupting association of monomeric components of the eIF4F heterotrimer or by antagonizing the interaction of the cap binding component of eIF4F, eIF4E, with the 7-methyl guanosine cap at the 5' end of the transcript.…”
Section: Approaches To Normalizing Deregulated Eif4f-mediated Translamentioning
confidence: 99%
“…The downstream effector proteins linking the cap-dependent translation initiation apparatus to the apoptotic machinery and the precise mechanisms regulating the translation of their cognate mRNAs are unknown. Prior studies have identified several candidate mRNAs encoding proteins subject to strong cap-dependent translational control that positively and negatively regulate cell viability including p53, Mdm-2, Fas/Apo-1, members of the Bcl-2 family, and cyclin D1 (33)(34)(35). Among these, we have recently shown that translational activation of cyclin D1 by eIF4E functions in the suppression of Myc-induced apoptosis (35).…”
Section: Activation Of Apoptosis By 4e-bp1 In Fibroblasts Expressingmentioning
confidence: 99%
“…Translation of the Bcl-xL protein has been demonstrated to be cap dependent (Polunovsky et al, 1996;Tan et al, 2000;Li et al, 2003). Cap-dependent translation initiation is a process regulated by mTOR through phosphorylation of its known target, 4E-BP1.…”
Section: Discussionmentioning
confidence: 99%